Politics of Commitment - Gupta, R. L (New Delhi, 1972)
The Fifth General Elections in India have been truly unique and historic in the annals of democratic countries in the world. For us, they constitute a significant landmark because they have inaugurated a new era in the contemporary Indian politics-an era of the POLITICS OF COMMITMENT. Though, every election has its own element of surprises, the mid-term poll in India has confounded every body-the prophets, the critics and the pessimists alike.
Keywords: Elections- India